Quality management systems for the food industry - Andrew Bolton (Blackie Academic and Professional, 1997)
The book describes what the standards are, what they mean and how to achieve them, and identifies both the potential benefits and limitations. It discusses choice of assessment house, whether to use consultants or not, and particularly out the detail that assessors will bo look for. Guidance is given on the basic format for a suitable quality management system